Implementation of Palu City Local Policy on Guidance and Control of Creative Field Traders - Selamet Riadi (Budapest International Research and Critics University, 2018)
The formulation of the problem in this research is how the implementation of policy of Guidance and Control of Field Creative Commerce in Palu City, while the purpose of this research is to know How to implement policy of Guidance and Control of Field Creative Trade in Palu City. The research method used is descriptive qualitative. The result of the research shows that the implementation of policy of Guidance and Control of Field Creative Commerce in Palu City has not been implemented well. It can be seen from communication indicator, resources, disposition and bureaucracy structure. Some aspects that still need to be improved as in the case of coordination among authorized agencies within the framework of arranging, fostering and controlling the Field Creative Traders are not mutually throwing responsibility in terms of their implementation. The approach undertaken to discipline the Field Creative Traders is still limited to persuasive approach and still only directed by the Official and Palu City of Palu. In addition, the provision of facilities and infrastructure such as places of sale must be provided in accordance with the wishes of the merchant that is to find a strategic place to sell.